ACTION OF ADVENTURE FORMULA IN MULAN 2020 - Zulfa Nur Azizah; Siti Awalia Maryani; Siti Hotimah Afriani (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2022)
Films that have action and adventure genres appeal to the audience by displaying scenes that have a sense of tension due to murders, resistance, and extreme actions played by the characters.Â This research focuses on the narrative and analysis formula fiction. The analysis conducted on the film Mulan 2020 aims to understand the fiction of action and adventure formula, as well as what the action functions in the adventure formula. The research data is in the form of information about film units related to the formulation of the problem which includes John G. Caweltiâ€™s four formulaic fictions, namely storylines, characters, settings, and situations contained in the animated film Mulan 2020. The data collection technique used in this study is the method of observation and literature study. The film Mulan 2020 is an adaptation of one of Disneyâ€™s animated live-action films of the same name. Overall, this film presents action and adventure that amazes and attracts the audience by displaying the martial arts skills of the main character. In each of her struggles, this film gives us a deep understanding of how the character Mulan fights for truth and freedom. And more interestingly, Mulan is a strong woman.